A fluorine-modified porous framework crystal material, a preparation method thereof, and acetylene / carbon dioxide separation application
By designing the fluorine-modified porous frame crystal material DZU-72-2F, the separation problem of acetylene and carbon dioxide is solved, and an efficient and energy-saving gas separation effect is achieved.
Patent Information
- Application Number
- CN202510151755.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-02-12
AI Technical Summary
It is difficult to efficiently separate acetylene and carbon dioxide in the prior art, especially when their physical properties are very similar, and the traditional separation methods have the disadvantages of high cost and high energy consumption.
By designing a fluorine-modified porous frame crystal material DZU-72-2F, the fluorine atom-modified ligand is used to adjust the MOF pore size and surface physical and chemical properties to achieve efficient and selective adsorption and separation of C2H2/CO2 mixed gas.
The material exhibits a high isothermal adsorption amount of nitrogen gas and a large specific surface area at a temperature of 77 K. The pore size distribution is suitable for the separation of acetylene and carbon dioxide, achieving efficient adsorption and separation of C2H2/CO2 mixed gas.
Smart Images

Figure CN119608128B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation and adsorption separation of crystalline porous framework materials, and relates to a fluorine-modified porous framework crystal material, a preparation method thereof, and acetylene / carbon dioxide separation application. Background Art
[0002] Acetylene is an important industrial raw material and is widely used in chemical production. It is mainly produced by cracking organic compounds or partial combustion of natural gas. However, these processes inevitably introduce carbon dioxide and other C1-C2 hydrocarbon impurities. In order to meet the industrial demand for high-purity acetylene, these impurities need to be deeply removed. However, since the physical properties of acetylene and carbon dioxide are very similar (for example, the boiling point of acetylene is 189.3 K, while that of carbon dioxide is 194.7 K), and the kinetic molecular diameters of the two are the same (both are 3.3 Å), the separation of the two has become one of the difficult problems in the field of chemistry.
[0003] Traditional separation methods, such as solvent extraction and cryogenic distillation, can achieve the separation of acetylene and carbon dioxide, but these methods have the disadvantages of high cost and high energy consumption. Therefore, the development of more efficient, energy-saving and environmentally friendly separation technologies has become a key research direction. Among them, porous materials are considered to be an ideal choice for acetylene purification due to their excellent gas adsorption properties.
[0004] Porous Metal-Organic Frameworks (MOFs) are a class of crystalline porous materials assembled from metal nodes and organic ligands, and have attracted widespread attention due to their unique structural properties. These materials have high porosity, structural diversity, and highly customizable pore functions, and are very promising solid adsorbents in the field of gas adsorption and separation. Studies have shown that by precisely controlling the pore size of MOF materials and modifying specific functional groups, their selective adsorption performance for low-concentration target gases can be significantly improved. This makes MOF materials show great application potential in the efficient separation of acetylene and carbon dioxide, providing a green and energy-saving solution for acetylene purification. Summary of the invention
[0005] The present invention provides a fluorine-modified porous framework crystal material, a preparation method thereof, and acetylene / carbon dioxide separation application. According to the size and chemical properties of C2H2 and CO2 molecules, the present invention uses fluorine-modified ligands to adjust the MOF pore size and surface physical and chemical properties to achieve efficient and selective adsorption and separation of C2H2 / CO2 mixed gases.
[0006] The present invention is achieved through the following technical solutions:
[0007] The first object of the present invention is to provide a fluorine-modified porous framework crystal material, the chemical formula of which is [Ni3OH(TMBTTP)(BDC-2F)3], named DZU-72-2F, wherein TMBTTP is an organic ligand 4,4',4'-(2,4,6-trimethylbenzene-1,3,5-triphenyl)tripyridine (CAS No.: 2027486-17-3), and H2BDC-2F is 2,5-difluoroterephthalic acid (CAS No.: 655-14-1); the porous framework material has a polyhedral cage structure modified with fluorine atoms.
[0008] Furthermore, from the perspective of framework connection construction, the crystal structure of DZU-72-2F belongs to the trigonal system, and the space group is P- 31 c , the unit cell parameters are: a = b = 16.9120(3) Å, c= 14.9727(5) Å, α = β= 90 o , γ= 120 o .
[0009] Furthermore, in the porous framework structure of DZU-72-2F, the crystallographic asymmetric structural unit comprises one Ni 2+ ion, 1 / 3 TMBTTP ligand, 1 / 3 µ3-O group, 1 BDC 2- -2F ligand;
[0010] Among them, Ni 2+ The ion is octahedrally coordinated with 6 atoms, including 4 from different BDCs. 2- -carboxyl O atom of the 2F ligand, 1 µ3-O atom, and 1 N atom from the TMBTTP ligand;
[0011] Three adjacent Ni 2+ The ion is represented by a µ3-O group and six different BDC 2- The six carboxyl groups of the -2F ligands bridge to form a typical trinuclear metal cluster [Ni3O(COO)6]; each metal cluster is connected to the BDC 2- The -2F ligands are alternately connected to form a three-dimensional structure with an acs topological configuration, and the TMBTTP ligands connect the [Ni3O(COO)6] clusters, further dividing them into a three-dimensional porous framework with a pacs topological structure.
[0012] Furthermore, in the framework structure of DZU-72-2F, there are two polyhedral cage structures. One is an anti-triangular prism polyhedron, whose upper and lower planes are each composed of one TMBTTP ligand, and the triangular vertices are composed of three [Ni3O(COO)6] clusters. The wall of the anti-triangular prism polyhedron is composed of six BDC 2- -2F occupation, the closest distance between the two bottom carbon atoms of the anti-triangular prism is 7.5 Å, and the closest distance between the two fluorine atoms of the opposite prismatic ligand is 12.8 Å;
[0013] The other is a triangular bipyramidal polyhedron, with one [Ni3O(COO)6] cluster occupying each of the upper and lower vertices, and three [Ni3O(COO)6] clusters evenly distributed in the middle. The vertices and the middle clusters are connected by BDC. 2- The three [Ni3O(COO)6] clusters in the middle are connected by -2F ligands, and the distance between the upper and lower vertex atoms of the triangular bipyramidal cage is 15 Å, and the distance between the triangular base atoms is 13.5 Å.
[0014] The present invention also provides a method for preparing the fluorine-modified porous framework crystal material, comprising the following steps:
[0015] The organic ligands H2BDC-2F and TMBTTP (0.02 mmol) were ultrasonically dissolved in DMA, the metal salt Ni(NO3)2·6H2O was dissolved in deionized water, the two solutions were mixed and 15 μl of 52 wt% tetrafluoroboric acid aqueous solution was added, and after sealing, a solvothermal reaction was carried out to obtain the fluorine-modified porous framework crystal material.
[0016] Furthermore, the molar ratio of the organic ligand H2BDC-2F and TMBTTP was (3-5):1, and every 1 mmol of H2BDC-2F corresponded to 10 ml of DMA.
[0017] Furthermore, the molar ratio of the organic ligand H2BDC-2F and Ni(NO3)2·6H2O is (0.83-1):1, and every 1 mmol of Ni(NO3)2·6H2O corresponds to 1.6-2 ml of deionized water.
[0018] Further, every 1 ml of DMA corresponds to 6.7-15 μl of 52 wt % tetrafluoroboric acid aqueous solution.
[0019] Furthermore, the temperature of the solvent thermal reaction is 90-110° C., and the reaction time is 24-72 hours.
[0020] Furthermore, the fluorine-modified porous framework crystal material is activated by the following method: first, the synthesized material is washed three times with ethanol, and the washed sample is immersed in anhydrous ethanol solution for 24 hours, during which the ethanol is continuously stirred and replaced three times. The sample is filtered to obtain a sample, and then dried in a vacuum oven at 80°C for 4 hours to obtain an activated sample.
[0021] The present invention also provides the application of the fluorine-modified porous framework crystal material in the adsorption and separation of C2H2 / CO2 mixed gas.
[0022] Beneficial technical effects of the present invention: The fluorine-modified porous framework crystal material of the present invention has a novel structure and a stable framework, and has two polyhedral cages: an anti-triangular prism and a triangular bipyramid. At 77 K, the nitrogen isotherm adsorption curve of DZU-72-2F is type I, and the maximum nitrogen adsorption at pressure P / P0 = 0.995 is 295 cm 3 / g, the specific surface area calculated from the adsorption data is 991 m 2 / g, and the pore size distribution obtained from adsorption data analysis is 4.5-12.0 Å. This permanent pore and suitable pore size as well as the pore surface environment modified by fluorine atoms can provide sufficient space and abundant binding sites for selective adsorption of gases, making the metal-organic framework suitable for the adsorption and separation of mixed gases. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a photo of DZU-72-2F crystal under a microscope.
[0024] Figure 2 This is a photo of DZU-72-2F in powder state.
[0025] Figure 3 This is the three-dimensional frame structure diagram of DZU-72-2F.
[0026] Figure 4 This is the structural diagram of the anti-triangular prism and triangular bipyramid polyhedron in DZU-72-2F.
[0027] Figure 5 The powder X-ray diffraction spectra of synthesized DZU-72-2F and its treatment under different conditions.
[0028] Figure 6 This is the thermal gravimetric curve of DZU-72-2F.
[0029] Figure 7 This is the nitrogen adsorption / desorption isotherm diagram of DZU-72-2F at 77 K.
[0030] Figure 8 The pore size distribution diagram calculated for the adsorption isotherm of DZU-72-2F.
[0031] Fig. 9 This is a comparison of the adsorption isotherms of C2H2 and CO2 on DZU-72-2F at 298 K.
[0032] Fig.10 This is a comparison of the adsorption isotherms of C2H2 and CO2 on DZU-72-2F at 273 K.
[0033] Fig.11 This is the C2H2 / CO2IAST selectivity curve of DZU-72-2F at 298 K.
[0034] Fig.12 This is the adsorption heat curve of DZU-72-2F for C2H2 and CO2.
[0035] Fig.13 Schematic diagram of the dynamic breakthrough curve of DZU-72-2F for C2H2 / CO2 at 298 K.
[0036] Fig.14 Schematic diagram of C2H2 molecules adsorbed in a triangular bipyramidal cage.
[0037] Fig.15 Schematic diagram of CO2 molecules adsorbed in an anti-triangular prism polyhedron cage.
[0038] Fig.16 Schematic diagram of the interaction between the DZU-72-2F skeleton and the C2H2 molecule.
[0039] Fig.17 Schematic diagram of the interaction between the DZU-72-2F skeleton and the CO2 molecule. DETAILED DESCRIPTION
[0040] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0041] Example 1
[0042] The organic ligand H2BDC-2F (0.1 mmol) and TMBTTP (0.02 mmol) were weighed and ultrasonically dissolved in 1 ml of DMA, and the metal salt Ni(NO3)2·6H2O (0.1 mmol) was dissolved in 0.2 ml of deionized water. Then 15 μl of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure-resistant container. The porous framework crystal material was obtained by thermal reaction at 90°C for 72 hours.
[0043] Example 2
[0044] The organic ligand H2BDC-2F (0.9 mmol) and TMBTTP (0.3 mmol) were weighed and ultrasonically dissolved in 9 ml of DMA, and the metal salt Ni(NO3)2·6H2O (1 mmol) was dissolved in 2 ml of deionized water. Then 100 μl of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure container bottle. The porous framework crystal material was obtained by thermal reaction at 100 °C for 24 hours.
[0045] Example 3
[0046] The organic ligand H2BDC-2OH (1 mmol) and TMBTTP (0.2 mmol) were weighed and ultrasonically dissolved in 10 ml of DMA, and the metal salt Ni(NO3)2·6H2O (1.2 mmol) was dissolved in 2 ml of deionized water. Then 120 μl of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure container bottle. The porous framework crystal material was obtained by thermal reaction at 100°C for 24 hours.
[0047] Example 4
[0048] The organic ligand H2BDC-2F (3 mmol) and TMBTTP (1 mmol) were weighed and ultrasonically dissolved in 30 ml of DMA, and the metal salt Ni(NO3)2·6H2O (3 mmol) was dissolved in 5 ml of deionized water. Then 200 μl of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure container bottle. The porous framework crystal material was obtained by thermal reaction at 110°C for 48 hours.
[0049] The products obtained in the above embodiments have the same morphology. Figure 1 The crystal morphology of DZU-72-2F obtained in Example 1-4 under a microscope. Figure 2 The green powder morphology of DZU-72-2F obtained in Example 1-4.
[0050] The product crystal structure and test results obtained in the above examples are the same, as shown below:
[0051] (1) Crystal structure determination:
[0052] Single crystals of appropriate size were selected under a microscope, and crystal data were collected at 150 K using a Bruker SMART APEXII CCD diffractometer. Absorption correction was performed using the SADABS program. SHELXL-2014 was used to solve and refine the structural data of F2 using the direct method and full matrix least squares method. The crystallographic program used the Olex2 integrated system to refine the occupancy of disordered C, F, and O atoms in the structure. All non-hydrogen atoms were refined anisotropically. The position and thermal parameters of hydrogen atoms were determined, and the structure was refined by geometric calculations. The disordered solvent molecules in the pores could not determine the structural model, so they were processed using the Mask program. The crystallographic data are shown in Table 1.
[0053] Table 1 Crystallographic data of metal organic framework materials
[0054]
[0055] Figure 3 The three-dimensional framework structure of DZU-72-2F shows that in DZU-72-2F, three adjacent Ni(II) ions are bound by a μ3-O group and six different BDCs. 2- The six carboxyl groups of the -2F ligands bridge to form typical trinuclear metal clusters [Ni3(μ3-O)(COO)6]. These trinuclear metal clusters are alternately connected with TMBTTP ligands to form a three-dimensional framework of PACs topology.
[0056] Figure 4 The structure diagram of the anti-triangular prism and triangular bipyramid polyhedron in DZU-72-2F shows that there are two polyhedral structures in the DZU-72-2F structure. The anti-triangular prism polyhedron has one TMBTTP ligand on the upper and lower planes, three [Ni3O(COO)6] clusters on the triangular vertices, and the wall of the anti-triangular prism polyhedron consists of six BDC 2- -2F occupies the space between the two bottom carbon atoms of the anti-triangular prism, and the closest distance between the two fluorine atoms of the prism ligand is 12.8 Å. The other is a triangular bipyramidal polyhedron, with one [Ni3O(COO)6] cluster occupying the upper and lower vertices respectively, and three [Ni3O(COO)6] clusters evenly distributed in the middle, with the vertices and the middle clusters connected by BDC. 2- The three [Ni3O(COO)6] clusters in the middle are connected by -2F ligands, and the distance between the upper and lower vertex atoms of the triangular bipyramidal cage is 15 Å, and the distance between the triangular base atoms is 13.5 Å.
[0057] Figure 5The X-ray powder diffraction spectrum shows that the prepared DZU-72-2F is a pure phase, and its crystal skeleton structure remains unchanged after the sample is activated by ethanol and cycled.
[0058] Figure 6 The thermogravimetric curves show that the thermal stability of the DZU-72-2F framework reaches 380 ℃.
[0059] (2) Specific surface area characterization
[0060] Figure 7 The DZU-72-2F frame material of the present invention is P / P N2 adsorption-desorption isotherms at 0 = 0.995 and 77 K. As can be seen from the figure, the saturated N2 absorption of DZU-72-2F reaches 295 cm 3 / g. By fitting and analyzing the adsorption data, the specific surface area of DZU-72-2F was found to be 991 m 2 / g.
[0061] Figure 8 It shows that the pore size distribution of DZU-72-2F is between 4.5 and 12 Å.
[0062] (3) Characterization of adsorption and separation performance:
[0063] Fig. 9 and Fig.10 For the DZU-72-2F frame material of the present invention at 298 K and 273 K, P= Adsorption isotherms of C2H2 and CO2 at 0.99 bar. Take 200 mg of the activated adsorbent sample and place it in vacuum at 100 °C for 3 h. After degassing, the gas adsorption isotherms were tested at 298 K and 273 K. It can be seen from the figure that under the conditions of 298 K and 0.99 bar, the maximum adsorption capacity of DZU-72-2F material for C2H2 and CO2 is 103.6 cm 3 / g, 58.5cm 3 / g. At 273 K, the maximum adsorption capacity of DZU-72-2F crystal material for C2H2 and CO2 is 120.5 cm 3 / g, 94.0 cm 3 / g. At 298K and 0.99 bar, the maximum adsorption amount difference exceeds 45 cm 3 / g.
[0064] Fig.11This is the IAST selectivity curve of the DZU-72-2F framework material of the present invention for C2H2 / CO2 mixed gas at 298 K. The figure shows that under the condition of 298 K, the IAST selectivity value of DZU-72-2F for C2H2 / CO2 is between 3.6 and 2.8.
[0065] Fig.12 The adsorption heat curves of DZU-72-2F framework material for C2H2 and CO2. Among them, the adsorption heat value of C2H2 is 31.0 kJ / mol, which is higher than the corresponding 27.0 kJ / mol of CO2. The above single-component gas adsorption results show that DZU-72-2F has a higher adsorption capacity and stronger affinity for C2H2 than CO2, and has the potential for selective adsorption and separation of C2H2 / CO2.
[0066] Fig.13 The penetration curve of the DZU-72-2F framework material of the present invention for separating C2H2 / CO2 mixed gas. At 298 K and a pressure of 1 bar, a C2H2 / CO2 mixed gas (C2H2 / CO2, v:v = 50 / 50) passes through a quartz tube containing 1.0 g of DZU-72-2F at a flow rate of 2 mL / min. From the penetration curve, it can be seen that CO2 first passes through the MOF material, and C2H2 gas molecules are detected after a certain interval. This further confirms the application ability of the material in adsorbing and separating C2H2 / CO2 mixed gas. The penetration time difference of the mixed gas in DZU-72-2F is 15.5 min. The results show that the porous metal organic framework material has the application potential for separating C2H2 / CO2 mixed gas.
[0067] (4) Analysis of adsorption separation mechanism:
[0068] Figure 14-17 Schematic diagram of the adsorption sites and host-guest interactions of C2H2 and CO2 molecules in the DZU-72-2F framework material calculated by density functional theory (DFT) in the present invention. Fig.14 and Fig.15 It shows that C2H2 and CO2 molecules are preferentially adsorbed in trigonal bipyramidal and anti-trigonal prism polyhedral cages, respectively. Fig.16 and Fig.17The interactions between the DZU-72-2F framework and C2H2 and CO2 molecules are shown. There are seven electrostatic interactions between the adsorbed C2H2 and the DZU-72-2F framework, including two C≡CH···F interactions with F atoms (2.80 and 3.97 Å), two CH···O interactions with carboxyl O atoms (2.94 and 2.99 Å), two C≡C···HC interactions with methyl H atoms (3.03 and 3.48 Å), and one C≡CH···N interaction with N atoms (2.95 Å). There are six C=O···H interactions (2.83 Å to 3.17 Å) between the CO2 molecule and the DZU-72-2F framework. Calculations show that the binding energy between the DZU-72-2F skeleton and C2H2 molecules is 38.0 kJ / mol, which is higher than the binding energy between it and CO2 molecules (28.1 kJ / mol). The above calculation results show that the fluorine atoms modified on the DZU-72-2F skeleton play a key role in improving its ability to adsorb C2H2 and separate C2H2 / CO2 mixed gases.
Claims
1. Application of a fluorine-modified porous framework crystal material in the adsorption and separation of C2H2 / CO2 mixed gas, characterized in that: The chemical formula is [Ni3OH(TMBTTP)(BDC-2F)3], wherein TMBTTP is an organic ligand 4,4',4'-(2,4,6-trimethylbenzene-1,3,5-triphenyl)tripyridine, and H2BDC-2F is 2,5-difluoroterephthalic acid; the fluorine-modified porous framework crystal material has a polyhedral cage structure modified with fluorine atoms; From the perspective of framework connection construction, the crystal structure of the fluorine-modified porous framework crystal material belongs to the trigonal system, and the space group is P- 31 c , the unit cell parameters are: a = b = 16.9120(3) Å, c= 14.9727(5) Å, α = β = 90 o , γ = 120 o ; In the structure of the fluorine-modified porous framework crystal material, the crystallographic asymmetric structural unit comprises one Ni 2+ ion, 1 / 3 TMBTTP ligand, 1 / 3 µ3-O group, 1 BDC 2− -2F ligand; Among them, Ni 2+ The ion is octahedrally coordinated with 6 atoms, including 4 from different BDCs. 2− -carboxyl O atom of the 2F ligand, 1 µ3-O atom, and 1 N atom from the TMBTTP ligand; Three adjacent Ni 2+ The ion is represented by a µ3-O group and six different BDC 2− The six carboxyl groups of the −2F ligands bridge to form a trinuclear metal cluster [Ni3O(COO)6]; each metal cluster is connected to the BDC 2− −2F ligands are alternately connected to form a three-dimensional structure with acs topology, and TMBTTP ligands connect [Ni3O(COO)6] clusters, further dividing them into a three-dimensional porous framework with pacs topology; In the structure of fluorine-modified porous framework crystal materials, there are two polyhedral cage structures: One is an anti-triangular prism polyhedron, with one TMBTTP ligand on each of its upper and lower planes, three [Ni3O(COO)6] clusters at the triangular vertices, and the wall of the anti-triangular prism polyhedron consisting of six BDC 2− For −2F occupation, the closest distance between the two bottom carbon atoms of the antitriangular prism is 7.5 Å, and the closest distance between the two fluorine atoms of the opposite prismatic ligand is 12.8 Å; The other is a triangular bipyramidal polyhedron, with one [Ni3O(COO)6] cluster occupying each of the upper and lower vertices, and three [Ni3O(COO)6] clusters evenly distributed in the middle. The vertices and the middle clusters are connected by BDC. 2− The three [Ni3O(COO)6] clusters in the middle are connected by -2F ligands, and the distance between the upper and lower vertex atoms of the triangular bipyramidal cage is 15 Å, and the distance between the triangular base atoms is 13.5 Å.
2. The use of the fluorine-modified porous framework crystal material according to claim 1 in the adsorption and separation of C2H2 / CO2 mixed gas, characterized in that: The method for preparing the fluorine-modified porous framework crystal material comprises the following steps: The organic ligands H2BDC-2F and TMBTTP were ultrasonically dissolved in DMA, the metal salt Ni(NO3)2·6H2O was dissolved in deionized water, the two solutions were mixed and then added with 52wt% tetrafluoroboric acid aqueous solution, and after sealing, a solvothermal reaction was carried out to obtain the fluorine-modified porous framework crystal material.
3. The use of the fluorine-modified porous framework crystal material according to claim 2 in the adsorption and separation of C2H2 / CO2 mixed gas, characterized in that: The molar ratio of the organic ligand H2BDC-2F and TMBTTP is (3-5):1, and 1 mmol of H2BDC-2F corresponds to 10 ml of DMA.
4. The use of the fluorine-modified porous framework crystal material according to claim 2 in the adsorption and separation of C2H2 / CO2 mixed gas, characterized in that: The molar ratio of the organic ligand H2BDC-2F and Ni(NO3)2·6H2O is (0.83-1):1, and every 1 mmol of Ni(NO3)2·6H2O corresponds to 1.6-2 ml of deionized water.
5. The use of the fluorine-modified porous framework crystal material according to claim 2 in the adsorption and separation of C2H2 / CO2 mixed gas, characterized in that: Each 1 mL of DMA corresponds to 6.7-15 μL of 52 wt% tetrafluoroboric acid aqueous solution.
6. The use of the fluorine-modified porous framework crystal material according to claim 2 in the adsorption and separation of C2H2 / CO2 mixed gas, characterized in that: The temperature of the solvent thermal reaction is 90-110° C., and the reaction time is 24-72 hours.
Citation Information
Patent Citations
In-situ preparation method of composite adsorbent
CN112871136A
Nickel-based double-ligand metal organic framework material, preparation method and application
CN115678027A
Hydroxyl-modified porous coordination polymer material, preparation method and sulfur dioxide capture application
CN119119508A